Conjoint Effect of Boron Nitride and Surface-Enhanced Flake Graphite in Thermal Conductivity of Thermally Conductive Grease - Xiong, Xiaojun; Li, Yifan (Journal of Research Updates in Polymer Science, 2023)
The next generation of high-power electronic devices is expected to exhibit improved heat dissipation capabilities despite their smaller size. Current studies have investigated the utilization of hybrid fillers, our study introduces a novel approach by combining boron nitride (BN) and surface-enhanced flake graphite (G), both of which possess a platelet-like structure, to develop a thermally conductive grease. The grease shows an exceptionally high thermal conductivity of 2.21 W/mK and an extremely low electrical conductivity of 7.3×10-6 S/m. The viscosity of the grease is measured at 149 Pa·s. By incorporating hybrid fillers with a significantly high aspect ratio into EPON 828, a notable reduction of interfacial thermal resistance is observed, which is attributed to the formation of an effective pathway for phonon transfer facilitated by the unique characteristics of the hybrid fillers. Various theoretical models are employed to corroborate the experimental data, which facilitates substantiating the fundamental principles underlying the enhanced thermal conductivity of the prepared thermal grease.